2017
DOI: 10.1017/s1751731117001057
|View full text |Cite
|
Sign up to set email alerts
|

Jugular-infused methionine, lysine and branched-chain amino acids does not improve milk production in Holstein cows experiencing heat stress

Abstract: Poor utilization of amino acids contributes to losses of milk protein yield in dairy cows exposed to heat stress (HS). Our objective was to test the effect of essential amino acids on milk production in lactating dairy cows exposed to short-term HS conditions. To achieve this objective, 12 multiparous, lactating Holstein cows were assigned to two environments (thermoneutral (THN) or HS) from days 1 to 14 in a split-plot type cross-over design. All cows received 0 g/day of essential amino acids from days 1 to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
1
19
2
Order By: Relevance
“…Under the conditions of this study, the 8D:6U treatment provided a balanced supply of AA in MP, which sustained high yields of ECM. Additionally, the balanced supply of AA reduces AA oxidation and plasma urea concentrations (Bach et al, 2000;Kassube et al, 2017). The latter contention is supported by lower MUN values observed from cows in the present study.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Under the conditions of this study, the 8D:6U treatment provided a balanced supply of AA in MP, which sustained high yields of ECM. Additionally, the balanced supply of AA reduces AA oxidation and plasma urea concentrations (Bach et al, 2000;Kassube et al, 2017). The latter contention is supported by lower MUN values observed from cows in the present study.…”
supporting
confidence: 80%
“…Even with new technologies and advances in heat abatement techniques, warm climates continue to present problems for lactating dairy cows (Ravagnolo et al, 2000). Reduction of RDP and RUP can potentially reduce some of the negative effects of heat stress on dairy cows (Kassube et al, 2017). Herein, the effects of RDP and RUP proportions are evaluated on intake, milk production, and N-use efficiency for primiparous and multiparous dairy cows exposed to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Sadri et al (2017) reported an increase in plasma concentration of Leu after a single duodenal bolus infusion of Leu at a dose of 0.15 g/kg of BW. On the other hand, Kassube et al (2017) did not find an increase in concentrations of free plasma BCAA after intravenous infusion of Met (12 g/d), Lys (21 g/d), and BCAA (35 g/d of Leu, 15 g/d of Ile, and 15 g/d of Val). Changes in the concentration of plasma free BCAA could be due to reduced DMI, BCAA absorption in the intestine or enhanced tissue uptake for catabolism or protein synthesis.…”
Section: Discussionmentioning
confidence: 64%
“…A subset of samples was selected to measure the concentration of plasma AA based on critical time points during the study (e.g., enrollment, time of biopsies, and beginning, middle, and end of the treatments). Plasma free AA concentrations were determined using EZ: faast (Phenomenex, Torrance, CA) by the chromatography and diagnostic services laboratory of the Veterinary Faculty, University of Montréal, as previously described (Kassube et al, 2017). Briefly, solid-phase extraction was followed by derivatization and a liquid/liquid extraction.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Concentrations of plasma free AA (EDTA samples on d −1 and 21 of the study) were measured using liquid chromatography coupled with mass spectrometry and a commercially available kit (Phenomenex EZ: faast, Torrance, CA) as previously described (Meesters et al, 2009;Ubhi et al, 2013;Kassube et al, 2017). Briefly, AA were removed from plasma using solid-phase extraction, derivatization, and liquid-phase extraction.…”
Section: Blood Collection and Analysesmentioning
confidence: 99%